EFFECT OF NUMERIC LITERACY ON MATHEMATICS OUTCOMES OF SEVENTH-GRADE STUDENTS OF SMP NEGERI 1 BRINGIN - Ahmad Aji Mustofa; Kimberly Queenia; Kiki Wicahyo; Miftachudin (Yayasan Amanah Nur Aman, 2026)
This study aims to determine how Effect Of Numeric Literacy On Mathematics Outcomes Of Seventh-Grade Students Of SMP Negeri 1 Bringin. The research employs a quantitative method with a design intended to examine the relationship between the variables studied. Data were collected from 32 students of class VII D through a numeracy literacy questionnaire and an analysis of their End-of-Semester Summative Assessment scores. The findings show that numeracy literacy has a very strong and significant relationship with mathematics learning outcomes. This is evidenced by a Pearson correlation value of 0.867 with a significance level of 0.000. The coefficient of determination () indicates that numeracy literacy accounts for approximately 75.1% of the variation in students’ mathematics performance. The regression analysis produced the equation Y = 1.125 + 1.016X, which suggests that numeracy literacy has a positive and significant effect on students’ learning outcomes. These results emphasize the importance of strengthening numeracy literacy, as it helps students better understand concepts, solve problems more effectively, and improve their mathematics achievement. The study recommends implementing contextual and numeracy-based learning approaches to enhance the quality of the learning process.